2001
DOI: 10.1007/s004050100380
|View full text |Cite
|
Sign up to set email alerts
|

Investigating quality of life and coping resources after laryngectomy

Abstract: Surgical procedures and in particular laryngectomy can become a life-saving treatment for patients with laryngeal or hypopharyngeal cancer, but can result in permanent damage. Clinical observation suggests that patients vary considerably in their ways of dealing with this new situation and in their ability to cope. The aim of our interdisciplinary group was to investigate the quality of life of laryngectomy patients and learn about their perceptions, situation and coping mechanisms. The development of an appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 25 publications
(31 reference statements)
1
28
0
1
Order By: Relevance
“…One additional explanation for the different results may be the wellknown coping abilities of cancer patients and their adaptation to living with the disease with time. 14,15 Our observations suggest that QOL is a complex concept and depends on factors other than olfaction.…”
Section: Commentmentioning
confidence: 96%
“…One additional explanation for the different results may be the wellknown coping abilities of cancer patients and their adaptation to living with the disease with time. 14,15 Our observations suggest that QOL is a complex concept and depends on factors other than olfaction.…”
Section: Commentmentioning
confidence: 96%
“…after tracheotomy), was interpreted in other studies as being due to coping abilities, adaptation to the postoperative situation or posttreatment response shift [6,7,15] .…”
Section: Discussionmentioning
confidence: 99%
“…The loss of voice can cause social, psychological and economical [20,21] disadvantages to the patients. Nalbadian et al [20] also reported that 30% of laryngectomees were ashamed of their condition, 42% stated that they were rather depressed, and 30% were feeling lonely.…”
Section: Discussionmentioning
confidence: 99%